MiR-340-5p Mediates Cardiomyocyte Oxidative Stress in Diabetes-Induced Cardiac Dysfunction by Targeting Mcl-1. (27th January 2022) - Zhu, Yinghong; Yang, Xuewen; Zhou, Jing; Chen, Long; Zuo, Pengfei; Chen, Lin; Jiang, Lan; Li, Ting; Wang, Dejiang; Xu, Yingyi; Li, Qiushi; Yan, Yi
Abstract : Diabetic cardiomyopathy (DCM) is initially characterized by early diastolic dysfunction, left ventricular remodeling, hypertrophy, and myocardial fibrosis, and it is eventually characterized by clinical heart failure. MicroRNAs (miRNAs), endogenous small noncoding RNAs, play significant roles in diabetes mellitus (DM). However, it is still largely unknown about the mechanism that links miRNAs and the development of DCM. Here, we aimed to elucidate the mechanism underlying the potential role of microRNA-340-5p in DCM in db/db mouse, which is a commonly used model of type 2 DM and diabetic complications that lead to heart failure. We first demonstrated that miR-340-5p expression was dramatically increased in heart tissues of mice and cardiomyocytes under diabetic conditions. Overexpression of miR-340-5p exacerbated DCM, which was reflected by extensive myocardial fibrosis and more serious dysfunction in db/db mice as represented by increased apoptotic cardiomyocytes, elevated ROS production, and impaired mitochondrial function. Inhibition of miR-340-5p by a tough decoy (TUD) vector was beneficial for preventing ROS production and apoptosis, thus rescuing diabetic cardiomyopathy. We identified myeloid cell leukemia 1 (Mcl-1) as a major target gene for miR-340-5p and showed that the inhibition of Mcl-1 was responsible for increased functional loss of mitochondria, oxidative stress, and cardiomyocyte apoptosis, thereby caused cardiac dysfunction in diabetic mice. In conclusion, our results showed that miR-340-5p plays a crucial role in the development of DCM and can be targeted for therapeutic intervention.